The Way of Life and Ecological Thinking of the Jambu Baru Community as a Foundation for Sustainable Peatland Management - Ismar Hamid; Arif Rahman Nugroho; Mahyuni Mahyuni; Rizky Ircham Muzaki; Nurul Khairin Fadiya; Indrawan Indrawan (JAMBURA GEO EDUCATION JOURNAL, 2023)
The existence, ecological thinking, and livelihood of local communities are often ignored in the management of peatlands for economic and protection purposes. This research aims to examine the way of life and ecological thinking of peat communities from a sustainable development perspective. The approach used is qualitative and type of case study research. Data was collected through participant observation, in-depth interviews, and documentation. Data were analyzed using the Miles and Huberman interactive model. The research found that the management of the natural resources of the peat ecosystem is the economic foundation of the community in Jambu Baru Village, which is manifested through various economic activities. The management is carried out to avoid the conversion of the peat ecosystem so that the condition of the peat ecosystem in the Jambu Baru Village area is still maintained and 93.69% of them still have high vegetation. Furthermore, the community moved collectively to reject the expansion of oil palm plantation companies targeting peatlands in Jambu Baru Village. Ecological thinking that exists in society is a manifestation of the sustainable development concept, which carries three dimensions of interest, namely ecological sustainability, social development, and economic development. Communities can realize these three dimensions of interest proportionally, and prove that peatlands are not marginal lands. Simply by managing the sources of life provided by the peat ecosystem with a sustainable approach, quality of life and intergenerational justice can be realized. Thus, strengthening the livelihoods of local communities is an approach that must be promoted to realize sustainable peatland management.